New Findings Regarding Day‐of‐the‐Week Returns over Trading and Non‐Trading Periods: A Note - ROGALSKI, RICHARD J. (Journal of Finance, 1984)
ABSTRACT This paper decomposes daily close to close returns into trading day and non‐trading day returns. We discover that all of the average negative returns from Friday close to Monday close documented in the literature for stock market indexes occurs during the non‐trading period from Friday close to Monday open. In addition, average trading day returns (open to close) are identical for all days of the week. January/firm size/turn‐of‐the‐year anomalies are shown to be interrelated with day‐of‐the‐week returns.